2007
DOI: 10.1136/jcp.2007.047688
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E confers a prognostic value in premenopausal breast cancer patients with tumours exhibiting an infiltrative growth pattern

Abstract: Cyclin E confers a prognostic value in premenopausal breast cancer patients with tumours exhibiting an infiltrative growth pattern.Berglund, Pontus; Stighall, Maria; Jirström, Karin; Rydén, Lisa; Fernö, Mårten; Nordenskjold, Bo; Landberg, Göran Link to publication Citation for published version (APA): Berglund, P., Stighall, M., Jirström, K., Rydén, L., Fernö, M., Nordenskjold, B., & Landberg, G. (2008). Cyclin E confers a prognostic value in premenopausal breast cancer patients with tumours exhibiting an infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…S1). Our cutoff values are similar to those previously adopted by other groups (30,31). The levels of cyclin E amplification and overexpression in breast tumors are lower than those described for HER2 (breast cancer) or MET (lung cancer) genes.…”
Section: Resultssupporting
confidence: 80%
“…S1). Our cutoff values are similar to those previously adopted by other groups (30,31). The levels of cyclin E amplification and overexpression in breast tumors are lower than those described for HER2 (breast cancer) or MET (lung cancer) genes.…”
Section: Resultssupporting
confidence: 80%
“…Most studies evaluating the association of cyclin E with histopathological markers have found correlation with aggressive features such as high grade and negative hormone receptor status [17,19,27], and some studies furthermore a correlation with high Ki67 expression, younger age at diagnosis and large tumour size [22,23,43]. The associations in our study were similar; high cyclin E correlated with high grade, high Ki67 expression and cyclin A expression, ER and PR negativity, large tumour size and younger age at disease onset.…”
Section: Discussionsupporting
confidence: 78%
“…Printed in Great Britain Endocrine-Related Cancer poorer overall survival or disease-free survival in ER+ or ER-patients, using a nuclear staining cyclin E antibody (Porter et al 2006). Using a nuclear/cytoplasmic staining antibody (raised against the HE12 epitope), Cyclin E1 did not predict for poor outcome in a cohort of 51 ER+ patients (Agarwal et al 2009), nor did it predict tamoxifen response (Berglund et al 2008).…”
Section: Cyclin E1 As a Biomarker For Er+ Breast Cancer And Endocrine Resistancementioning
confidence: 95%